Molecular Detection of Chicken Infectious Anaemia Virus from Backyard Chickens in Libya - Al-Kateb A1*, Mansour L2, Skeeb A3, Al-Khallab E4, Dardour A5; Gerish E KH6. (AlQalam Journal of Medical and Applied Sciences, 2017)
Background and Objective: Chicken infectious anaemia (CIA) is primarily a disease of young chickens caused by a small DNA virus - chicken infectious anaemia virus (CIAV) belonging to the family Circoviridae. The virus is present in all major poultry producing countries of the world. The vertical transmission, SPF/vaccine contamination, highly contagious, hardy and omnipresent nature and also the potential for inducing marked immunosuppression has placed the CIAV at a global scenario reflecting considerable economic significance. In recent years, the virus has been detected and isolated from commercial chicken flocks of Libya. Moreover there is scarcity of information on epidemiological status of the infectious diseases in backyard chickens (Gallus gallus domesticus) in the Libya. Therefore the molecular detection of circulating CIAV among backyard chickens was evaluated in the current study for the first time in Libya. Methods: During March 2014, two pooled homogenised samples (consists of; thymus and spleen) from village chickens were collected then stored by using Flinders Technology Associates (FTA) filter paper for DNA extraction. Polymerase chain reaction (PCR) technique was undertaken on the samples using a pair of primers designed to amplify a 1390 base pair fragment in the VP1 (capsid protein) gene of CIAV. Results: The presence of the expected amplification products obtained by PCR was confirmed by agarose gel electrophoresis. PCR analysis detected CIAV-DNA in the two (100%) tested tissue samples. Conclusion: Apart from the previous report of serologic evidence of CIAV infection in Libyan backyard chickens, the demonstration of CIAV from naturally infection in these type of chickens has not been reported before in different breeding regions countrywide. The present report revealed presence of CIAV in study population and it could be regarded as a potential threat to chickens raising at the studied area. Under no circumstance should commercial industrial chicken varieties be allowed to come into direct or indirect contact with backyard chickens, and vice-versa. The findings of this study suggest that continuous CIAV surveillance and genetic analysis at commercial chicken and free range flocks are imperative.